Comparison of Laparoscopic Sacrocolpopexy and Vaginal Sacrospinous Ligament Fixation Techniques Applied Concomitantly in Patients Undergoing Vaginal or Laparoscopic Hysterectomy for Uterovaginal Pelvic Prolapse - Ömer Ünal; Ozan Karadeniz (IMR Press, 2023)
Background: The aim of this study was to investigate patients having pelvic organ prolapse (POP) stage 2 and greater who have undergone vaginal hysterectomy concomitant with sacrospinous ligament fixation (VAH + SLF) or total laparoscopic hysterectomy concomitant with sacrocolpopexy (TLH + SCP) in terms of quality of life, sexual function, major or minor complications, and cure rates. We also aimed to determine which procedure is superior according to the results of the cases in which TLH + SCP and VAH + SLF were applied. Methods: A retrospective cohort study was conducted at a tertiary center, including 137 patients who underwent vaginal or laparoscopic hysterectomy for symptomatic uterine prolapse with a pelvic organ prolapse quantification system (POP-Q) score ≥2 and who underwent sacrospinous fixation (n = 90) or laparoscopic sacrocolpopexy (n = 47) concomitantly between January 2017 and May 2022. The Turkish-validated Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12) and the Prolapse Quality of Life Questionnaire (P-QoL) were asked to be completed prior to surgery, on the 30th postoperative day, at six months, and at one year. Results: There was no statistically significant difference among groups regarding the scores of the PISQ-12 and P-QoL questionnaires. The TLH + SCP group had a longer operative time (108 vs. 94 min, p = 0.037). A statistically significant difference was found in blood loss between the operations, favoring the TLH + SCP group (p = 0.038). Postoperative 6th-hour visual analog scale values were significantly higher in the TLH + SCP group (p = 0.01). Two women (2.2%) in the VAH + SLF group had a recurrence within one year postoperatively versus none in the TLH + SCP group (p = 0.038). Conclusions: The TLH + SCP group had the same decrease in subjective outcomes (PISQ-12 and P-QoL), whereas the VAH + SLF group had a lower major complication rate than the TLH + SCP group. There is a need for a prospective, multicenter, randomized controlled study with multiple patients and long-term follow-up results to understand the ideal form of vaginal cuff suspension following a hysterectomy.